2002
DOI: 10.1080/0954012021000005443
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported physical health among older surrogate parents to children orphaned and affected by HIV disease

Abstract: Around the globe, older relatives, largely grandparents, have become the surrogate parents to children and adolescents orphaned by parental death from HIV/AIDS and to those whose infected parents are too ill to serve as their primary caregivers. Largely invisible to research, programme and policy initiatives, these older surrogate parents face compounded stress and the risk of neglected and compromised health. An exploratory study of third- and fourth-generation relatives (n=20, mean of 59 years) found an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…Children living with grandparents tended to report better HRQL than others, especially in psychosocial domains. This was beyond our expectation and inconsistent with previous studies conducted in other countries (Joslin & Harrison, 2002; Juma et al, 2004; Ozuah, 2003). We found that caregivers spending more hours accompanying the child appeared to increase the child’s psychosocial health.…”
Section: Discussioncontrasting
confidence: 99%
“…Children living with grandparents tended to report better HRQL than others, especially in psychosocial domains. This was beyond our expectation and inconsistent with previous studies conducted in other countries (Joslin & Harrison, 2002; Juma et al, 2004; Ozuah, 2003). We found that caregivers spending more hours accompanying the child appeared to increase the child’s psychosocial health.…”
Section: Discussioncontrasting
confidence: 99%
“…Parents find it hard to combine work with taking care of an ill child; 24 especially mothers have a need to compromise between gainful employment and taking care of the ill child 53 . Seventy per cent of elderly close relatives who are acting as primary caregivers report that they have too little time for taking care of their own health and their own health is often experienced as bad 54 …”
Section: Resultsmentioning
confidence: 99%
“…Another reason for the geographic limitation in writing on the present issue might be priorities of needs. When resources are limited, food, shelter and medicine will be more important to satisfy than other needs, and research focused on the needs of relatives will probably receive even lower priority 9,27,54 . The literature search was limited to the last 5 years and only to two databases, implying that there might be research and additional knowledge that is not included in this work.…”
Section: Discussionmentioning
confidence: 99%
“…17 The resulting burden on these aunts and grandmothers is substantial; it can result in economic deprivation, and deterioration of their own health from the physical challenges of caring for young children. 18,19 Hlengiwe, who was caring for seven children as well as a partner on ART, gave up taking care of herself. She was demoralized by the change in her body shape, the disrespectful attitude of nurses, and a nephew who was trying to evict her from the family home.…”
Section: Negative Survival Strategiesmentioning
confidence: 99%